Gender Differences in the Prevalence of Parkinson's Disease. Issue 1 (14th November 2022) - Zirra, Alexandra; Rao, Shilpa C.; Bestwick, Jonathan; Rajalingam, Rajasumi; Marras, Connie; Blauwendraat, Cornelis; Mata, Ignacio F.; Noyce, Alastair J.
ABSTRACT: Background: Parkinson's disease (PD) affects males more than females. The reasons for the gender differences in PD prevalence remain unclear. Objective: The objective of this systematic review and meta‐analysis was to update the overall male/female prevalence ratios (OPR). Methods: We updated previous work by searching MEDLINE, SCOPUS, and OVID for articles reporting PD prevalence for both genders between 2011 and 2021. We calculated OPRs and investigated heterogeneity in effect estimates. Results: We included 19 new articles and 13 articles from a previously published meta‐analysis. The OPR was 1.18, 95% CI, [1.03, 1.36]. The OPR was lowest in Asia and appeared to be decreasing over time. Study design, national wealth, and participant age did not explain OPR heterogeneity. Conclusion: Gender differences in PD prevalence may not be as stark as previously thought. Studies are needed to understand the role of other determinants of gender differences in PD prevalence.